The rethink about the market for corporate control in United Kingdom - He, Zhao; Zou, Zhiqiang; Yang, Ruiqi (Eximia, 2025)
The market for corporate control is a market-based mechanism, it plays an important role in corporate governance. It will discuss the history of the market for corporate control and relevant takeover regulations in UK. It shows that the attitude of the UK government towards takeover has changed dramatically because of the market for corporate control, and the government may trust and rely on it excessively. However, numerous potential issues of the market for corporate control may be ignored by the British government and shareholders. Firstly, it may not maximize shareholders’ value well in practice. Besides, it also may not optimize resource allocation well in UK. Finally, it may ignore the interests of employees, and they still could not get enough protection. Above problems request the UK government to take more feasible measures to regulate takeovers, and fill the loopholes of the market for corporate control, otherwise, it will hinder the healthy development of British economy. Finally, it suggests the UK government to take measures from three aspects, more eligible bidders, more eligible targets and build a rational takeover process.